Surface treatment effect in thermoplastic rubber and natural leather for the footwear industry - R. M. M. Paiva (2015)
This paper aims to analyze the peel strength of an adhesive joint with various types of surface treatments. In the shoe industry, the adhesive properties are very important to ensure the quality of manufacture of the shoe, thus, to better understand the behaviour of the adhesive joint, it is important to analyze the peel resistance in order to adjust the manufacturing process. In this work, natural leather, thermoplastic rubber (TR) and a non-structural, solvent based, polyurethane adhesive were considered. The influence of the application of chemical and/or mechanical surface treatments on substrates in the peel strength of a T joint were analysed. To characterize the surfaces, several test were considered, including Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscope (SEM) and contact angle measurements. It was found that certain surface treatments are required to obtain an adhesive joint capable of satisfying the minimum strength requirements of the shoes sector.